FINANCIAL DISTRESS, PROFITABILITY, CAPITAL INTENSITY AND TAX AVOIDANCE - Matitaputty, Jean Stevany; Ramadhan, Raihan Gilang (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2023)
This study aims to investigate the effect of financial distress, profitability, and capital intensity on tax avoidance using a quantitative approach with secondary data. The data were collected through purposive sampling of companies listed in the LQ45 ranking on the Indonesia Stock Exchange over a period of three years from 2019 to 2021. The results indicate that financial distress, as measured by Z-score, has a positive effect on tax avoidance, while profitability and capital intensity have a negative effect on tax avoidance, as measured by Cash Effective Tax Rate (CETR). This research contributes to the body of knowledge in the field of taxation, specifically in the area of tax avoidance.